2018
DOI: 10.1175/jhm-d-18-0080.1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of the IFloodS Radar Rainfall Products for Hydrologic Applications

Abstract: This study describes the generation and testing of a reference rainfall product created from field campaign datasets collected during the NASA Global Precipitation Measurement (GPM) mission Ground Validation Iowa Flood Studies (IFloodS) experiment. The study evaluates ground-based radar rainfall (RR) products acquired during IFloodS in the context of building the reference rainfall product. The purpose of IFloodS was not only to attain a high-quality ground-based reference for the validation of satellite rainf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…It is because the quantitative estimation of the radar rainfall retrievals strongly influences model results. Studies with physically-based models have focused on two main sources of uncertainty: uncertainty in rainfall input [188][189][190] originated from the systematic errors produced in the process of Z-R transformation, and uncertainty in model parameters [191,192]. Investigations on radar hydrology are more frequently focused on rainfall input uncertainty.…”
Section: Uncertainty In Radar Estimates For Hydrological Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is because the quantitative estimation of the radar rainfall retrievals strongly influences model results. Studies with physically-based models have focused on two main sources of uncertainty: uncertainty in rainfall input [188][189][190] originated from the systematic errors produced in the process of Z-R transformation, and uncertainty in model parameters [191,192]. Investigations on radar hydrology are more frequently focused on rainfall input uncertainty.…”
Section: Uncertainty In Radar Estimates For Hydrological Modelingmentioning
confidence: 99%
“…In a trade-off between the added error of the radar rainfall derivation chain and the improvement on the radar rainfall estimates, the bias adjustment by means of rain gauge networks has been extensively accepted for applications on radar hydrology, while efforts have been made to reduce the negative effects of relative calibration on radar composites, as in Seo et al [193]. For instance, uncertainty in radar rainfall estimates was evaluated by Seo et al [188] using different radar rainfall products that differ on the data composition (i.e., only radar-based product vs. rain gauge bias-adjusted radar product). The study demonstrated the need for bias-adjusted radar estimates related to the Iowa Flood Studies (IFloodS) experiment.…”
Section: Uncertainty In Radar Estimates For Hydrological Modelingmentioning
confidence: 99%
“…The 2DVD was the primary instrument used in this study to derive the relationships between the radar observables and gamma DSD parameters. The datasets included four GPM field campaigns: the Midlatitude Continental Convective Clouds experiment (MC3E) (Jensen et al 2016); the Iowa Flood Studies (IFloodS) (Seo et al 2018); the Integrated Precipitation and Hydrology Experiment (IPHEx) (Duan et al 2015); the Olympic Mountain Experiment (OLYMPEx) (Houze et al 2017); and extended (longer than 1 year) data collections made at two NASA facilities: Marshall Space Flight Center, University of Alabama at Huntsville (MSFC-UAH), and NASA Goddard Space Flight Center Wallops Flight Facility (GSFC-WFF). These datasets represent a range of midlatitude meteorological regimes including midcontinental deep convection (MC3E), flood-producing frontal and mesoscale convective systems (IFloodS), warm-season Appalachian area orographic enhancements from valley to mountain (IPHEx), West Coast cold-season orographic enhancements from ocean to mountain (OLYMPEx), as well as a year-long sampling of midlatitude continental inland (MSFC-UAH) and coastal mid-Atlantic region precipitation (GSFC-WFF).…”
Section: Databasementioning
confidence: 99%
“…limited only to the observational and estimation errors). In reality, the rainfall forecasts are subject to considerable uncertainty, especially for the longer lead times (e.g., Seo et al 2018).…”
Section: Closing Commentsmentioning
confidence: 99%